2020
DOI: 10.2147/dddt.s262816
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emodin Reverses the Epithelial–Mesenchymal Transition of Human Endometrial Stromal Cells by Inhibiting ILK/GSK-3β Pathway</p>

Abstract: Purpose To explore the exact mechanism through which emodin down-regulates the migration and invasion abilities of endometrial stromal cells. Moreover, to explore the theoretical basis of emodin in the treatment of endometriosis. Patients and Methods Endometriosis endometrial stromal cells (EESs) were cultured from 15 women with endometriosis and control endometrial stromal cells (CESs) were cultured from 12 women without endometriosis. The levels of proteins were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Accordingly, the subsequent experiment revealed higher expression levels of lncRNA BANCR in Ect-ESCs relative to eutopic ESCs ( P < 0.05, Figure 1(c) ). Several studies have documented that suppression of abnormal proliferation or invasion of ESCs mitigates EM progression [ 33 35 ]. To further explore the role of lncRNA BANCR in ESC proliferation and invasion, Ect-ESCs were transfected with si-BANCR (si-BANCR#1 and si-BANCR#2) to downregulate lncRNA BANCR expression ( P < 0.05, Figure 1(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the subsequent experiment revealed higher expression levels of lncRNA BANCR in Ect-ESCs relative to eutopic ESCs ( P < 0.05, Figure 1(c) ). Several studies have documented that suppression of abnormal proliferation or invasion of ESCs mitigates EM progression [ 33 35 ]. To further explore the role of lncRNA BANCR in ESC proliferation and invasion, Ect-ESCs were transfected with si-BANCR (si-BANCR#1 and si-BANCR#2) to downregulate lncRNA BANCR expression ( P < 0.05, Figure 1(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation, invasion, and migration of ESCs are of vital significance in the onset of EM 23,24 . To assess the functionality of METTL3 on Ect‐ESCs, we successfully upregulated METTL3 in the Ect‐ESCs ( p < 0.01, Figure 2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferation, invasion, and migration of ESCs are of vital significance in the onset of EM. 23,24 To assess the functionality of METTL3 on Ect-ESCs, we successfully upregulated METTL3 in the Ect-ESCs (p < 0.01, Figure 2A,B). Our results showed that after METTL3 overexpression, the proliferation potential of Ect-ESCs was significantly reduced (p < 0.01, Figure 2C,D) along with notably decreased numbers of invasive and migrative Ect-ESCs (p < 0.01, Figure 2E,F).…”
Section: Mettl3 Overexpression Restrains the Proliferation Invasion A...mentioning
confidence: 99%
“…Four compounds, apigenin, curcumin, genistein, and quercetin, were identified as antagonists for embryo implantation [124][125][126][127][128][129][130]. Four compounds, berberine, emodin, paeoniflorin, and γ-tocotrienol, increased implantation rates by increasing endometrial receptivity or decidualization [103,116,120,131,132]. In contrast, resveratrol has been shown to have dual effects as an agonist and antagonist [133,134].…”
Section: Potential Involvement Of Autophagic Regulation On the Effect Of Natural Products As Embryo Implantation Enhancermentioning
confidence: 99%